2008
DOI: 10.1111/j.1469-7998.2008.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐spatial organization of urban stone martens

Abstract: Stone martens Martes foina are common occupants of urban environments across continental Europe. We predicted that like other 'urban adapters', urban stone martens should exhibit smaller home ranges, more extensive home-range overlap and higher population densities than their rural counterparts. We radio-tracked 13 stone martens (10 females, three males) in two towns in southern Luxembourg during a 2-year period, in order to investigate nocturnal ranging behaviour. All martens maintained stable, year-round ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Therefore, the species showed no apparent selection in relation to urbanization. In other European regions the stone marten is highly synanthrophic (Libois andWaecheter 1991, Broekhuizen andMuskens, 2000;Herr et al, 2009;Tóth et al, 2009), something that has been not observed in a previous research in the Iberian region of the Mediterranean (Virgós and Casanovas, 1998;Virgós and García, 2002). Therefore, the stone marten seems to be more flexible in this region to different types of landscapes than its Centroeuropean counterparts (see also Virgós et al, 2000;Tóth et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the species showed no apparent selection in relation to urbanization. In other European regions the stone marten is highly synanthrophic (Libois andWaecheter 1991, Broekhuizen andMuskens, 2000;Herr et al, 2009;Tóth et al, 2009), something that has been not observed in a previous research in the Iberian region of the Mediterranean (Virgós and Casanovas, 1998;Virgós and García, 2002). Therefore, the stone marten seems to be more flexible in this region to different types of landscapes than its Centroeuropean counterparts (see also Virgós et al, 2000;Tóth et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…raccoons, mustelids; Prange et al 2003, Herr et al 2008, TÓth et al 2011, Červinka et al 2014 are frequently higher in urban environments compared to adjacent, more natural habitats (Rodewald et al , Šálek et al 2015. The results of growing number of monitoring studies demonstrate that many predatory species have the ability to adapt to and gain from human altered landscapes and have increased their urban populations recently.…”
Section: Changes In Consumer-based Forcesmentioning
confidence: 99%
“…The models were based on four assumptions: (1) Occupancy of smaller and more isolated montado patches is influenced by the effective distance to larger montado source areas, and this effect will become evident over time; (2) effective distances are dependent on different land use patterns with different resistance values; (3) roads are not likely to serve as barriers to movement; stone marten are known to cross roads (Grilo et al 2009) and travel along streets in urban areas (Herr et al 2009); and (4) water bodies have a negligible effect on carnivore movements due to their small size and limited number in the study area. We therefore assumed that different land cover types influenced stone marten movements and chose not to include roads or water bodies as landscape elements.…”
Section: Discussionmentioning
confidence: 99%